“Partiu estágio!” Experience report of a nursing student (Research, Society and Development, 2021)
Objective: Learn, from the experience report of an academic from the Bachelor's Degree in Nursing, the contributions that the state government program, “Partiu Estágio”, provided in her academic training and identify the gaps in the execution of said program. Method: This is a qualitative, descriptive study, type report of the experience, that occurred in a hospital of a bahian city, through the “Partiu Estágio” program. Results: The experiences lived during the period from April 2018 to April 2019, ensured the academic a differentiated formation in the reality of the Unified Health System, among them we can list the Public-Private Partnership. Conclusion: This experience enriched her personal and professional formation by enabling her to overcome challenges, overcome adverse situations and make decisions, resulting in the improvement of critical sense and interpersonal interaction in the work environment. So, the relevance of the participation of academics in extracurricular internship programs is to enable critical-reflective formation, prioritizing the principles and guidelines of the Unified Health System, in addition to the need to expand dialogues between the management of internship programs of the state government, with the institutions of higher education and granting institutions of the internship.